Methods for justifying the construction of settlement bypasses based on traffic flow regimes and road capacity - Ugnenko, Yevgeniia; Uzhviieva, Elena; Sorochuk, Nataliia; Korostelov, Yevhen; Shevchenko, Anna; Bielikova, Nataliia (International Conference “Environmental Engineering”, 2026)
To justify the construction of bypasses around settlements, it is necessary to conduct a thorough analysis of vehicle traffic intensity on the access roads leading to these settlements. When determining the feasibility of bypass construction, selecting the direction of the route, and defining its geometric parameters, detailed information on the intensity of transit vehicle flows and the directions of their origin-destination correspondences is required. These parameters are influenced by the administrative and economic significance of the settlement, the classification of the adjoining roads, the structure of transport connections, and the geographical location. In analyzing the mathematical model of the “road conditions – traffic flow – settlement” system, it is important to select appropriate types of vehicle speeds to formalize various elements of the subsystems. The choice of speed indicator depends on the specific goals and tasks of the modeling process. To adequately describe the “road conditions – traffic flow – settlement” system, it is necessary to consider the design speed, the average instantaneous speed of the traffic flow, and the average link (route) speed over a given section. The results of a comparative analysis of traffic flow assessment models demonstrate that most models used for justifying the construction of settlement bypasses are based on a phase-based representation of the transitions in the qualitative states of the traffic flow.